PENGARUH PENERAPAN STATEGI PEMBELAJARAN AKTIF TIPE LISTENING TEAM TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS XI IPS SMAN 2 BAYANG - Sulastri, Rini; Zulfaneti, Zulfaneti; Febriana, Rina (Pendidikan Matematika, 2014)
ABSTRACTThis research was conducted based on the fact indicating that the studentsâ understanding on mathematics concept was`stiil low, and the students had less concern on the teacherâs explanation. This research was aimed at revealing whether the use of Listening Team active learning strategy could give better effect on the studentsâ understanding on mathematics concept than that of the conventional learning in class XI IPS SMAN 2 Bayang. This was an exsperimental research which used random sampling technique. In this research class XI IPS.3 was`chosen as the experimental class, and class XI IPS.4 as the control one.the instrument of the research was a post-test. The test was in the form of essay whose r11 was 0,819. The data gotten was analyzed by using t-test assisted with MINITAB. Based on the result of hypothesis test, it was found that P-value (0,000) was smaller than Î± (0,05) indicating that the hypothesis was accepted. Thus, it was concluded that the use of Listening Team active learning strategy could improve the studentâ understanding on mathematics concept better than that of the conventional learning in class XI IPS of SMAN 2 Bayang.